Nuclear factor (NF)‐κB and its associated pathways are major molecular regulators of blood‐induced joint damage in a murine model of hemophilia. Issue 2 (7th February 2013) - Sen, D.; Chapla, A.; Walter, N.; Daniel, V.; Srivastava, A.; Jayandharan, G. R.
Summary Background The present study was designed to investigate the molecular signaling events from onset of bleeding through the development of arthropathy in a murine model of hemophilia A. Methods and results A sharp‐injury model of hemarthrosis was used. A global gene expression array on joint‐specific RNA isolated 3 h post‐injury revealed nuclear factor‐kappa B (NF‐κB) as the major transcription factor triggering inflammation. As a number of genes encoding the cytokines, growth factors and hypoxia regulating factors are known to be activated by NF‐κB and many of these are part of the pathogenesis of various joint diseases, we reasoned that NF‐κB‐associated pathways may play a crucial role in blood‐induced joint damage. To further understand its role, we screened NF‐κB‐associated pathways between 1 h to 90 days after injury. After a single articular bleed, distinct members of the NF‐κB family (NF‐κB1/NF‐κB2/RelA/RelB) and their responsive pro‐inflammatory cytokines (IL−1β/IL−6/IFNγ/TNFα) were significantly up‐regulated (> 2 fold, P < 0.05) in injured vs. control joints at the various time‐points analyzed (1 h/3 h/7 h/24 h). After multiple bleeds (days 30/60/75/90), there was increased expression of NF‐κB‐associated factors that contribute to hypoxia (HIF‐1α, 3.3−6.5 fold), angiogenesis (VEGF‐α, 2.5−4.4 fold) and chondrocyte damage (matrix metalloproteinase−13, 2.8−3.8 fold) in the injured joints. Micro RNAs (miR) that are known to regulate NF‐κB activation (miRs‐9 and 155), inflammation (miRs‐16, 155 and 182) and apoptosis (miRs‐19a, 155 and 186) were also differentially expressed (−4 to +13‐fold) after joint bleeding, indicating that the small RNAs could modulate the arthropathy phenotype. Conclusions These data suggest that NF‐κB‐associated signaling pathways are involved in the development of hemophilic arthropathy.